Level of dietary practices and frequency of physical activity - Villafuerte Arias, Jorge; Coloma Guerrero, Carla; Gómez Espinoza, Leonel; Enríquez Jácome, Miguel Ángel; Chávez Arizala, Jenrry Fredy (Salud Integral y Comunitaria, 2025)
Introduction: dietary practices have been a fundamental issue in the area of public health, because they play a vital role in the prevention of deficiency or excess diseases.Objective: this research aims to determine the level of dietary practices and the frequency of physical activity in the province of Santo Domingo de los Tsáchilas - Ecuador 2021.Method: a quantitative, non-experimental, descriptive and correlational, and cross-sectional study was applied with a simple probabilistic sample of 692 inhabitants.Results: the majority of respondents are men (59.5%) and single (68.8%). Protein consumption is mostly medium (65.5%), while carbohydrate consumption is high (76.3%), which can increase the risk of being overweight. Vegetable consumption is medium (55.4%), and dairy consumption is also mostly medium (44.4%). Liquid consumption is similar between medium (41.5%) and high (42.1%) levels. As for fruit, 52.6% consume it regularly. Healthy eating habits are medium (40.9%), and 45.2% engage in physical activity, although there is a notable risk of sedentary lifestyle (36.7%).Conclusions: The study shows a male and single profile among the respondents. Although protein and vegetable intake is medium, high carbohydrate consumption and low fluid intake pose risks of overweight and dehydration. Most consume fruit, but eating habits are medium. It is recommended to promote healthier habits and increase physical activity.